2014
DOI: 10.1186/1477-7827-12-85
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34 family expression in bovine gametes and preimplantation embryos

Abstract: BackgroundOocyte fertilization and successful embryo implantation are key events marking the onset of pregnancy. In sexually reproducing organisms, embryogenesis begins with the fusion of two haploid gametes, each of which has undergone progressive stages of maturation. In the final stages of oocyte maturation, minimal transcriptional activity is present and regulation of gene expression occurs primarily at the post-transcriptional level. MicroRNAs (miRNA) are potent effectors of post-transcriptional gene sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 45 publications
2
55
0
3
Order By: Relevance
“…; Tscherner et al. ). These facts indicate that an aberrant expression in spermatozoa could have implications at least during early stages of pregnancy.…”
Section: Resultsmentioning
confidence: 97%
“…; Tscherner et al. ). These facts indicate that an aberrant expression in spermatozoa could have implications at least during early stages of pregnancy.…”
Section: Resultsmentioning
confidence: 97%
“…It has been demonstrated that all the members of miR-34 family (i.e. miR-34a, -34b and -34c) are found in bovine sperm (Tscherner et al 2014). Additionally, miR-34c seems to be important for the later steps of spermatogenesis because it is highly expressed in mouse pachytene spermatocytes and round spermatids in murine testis by targeting the activating transcription factor 1 (ATF1; Liang et al 2012).…”
Section: Functions Of Mirnas In Meiosis and Spermiogenesismentioning
confidence: 99%
“…In several species, miR-34 may be involved in early embryonic development (4,15,16), and sperm-borne miR-34c has been reported to be important for the first cleavage division of mouse embryo, via the modulation of B-cell lymphoma-2 expression (15). However, the impact of spermatozoa miR34b/c on human embryonic development has not been explored.…”
mentioning
confidence: 96%
“…However, the paternal contribution to the zygote increasingly is being recognized. Several transcripts that are present in human spermatozoa and zygotes are absent in unfertilized oocytes, suggesting that spermatozoa deliver these transcripts to oocytes during fertilization, and that they may play a role in subsequent zygote and embryonic development (3 (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation